PARADIGMA BERFIKIR NAHDATUL ULAMA DAN GAGASAN MODERASI - Usman, Muh. Ilham (AL-Fikr, 2015)
This article elaborates on the paradigm of thinking Nahdlatul Ulama as one of the largest religious organization in Indonesia. NU was born officially in 1926, but was preceded by a forerunner of several organizations, the Nahdlatul Tujjar, Tashwirul Afkar and Nahdlatul Wathan. These organizations that generate and shape of NU. NU was born and formed to save every human individual from the divisions and unite in upholding commanding the good and forbidding the evil. Appropriate understanding of the basic principles of religion which was built by NU born in accordance with the requirements and can be used in view of todays reality, then prudence is indispensable to it. It is necessary, not to close the door of ijtihad, and not also in order to liberalize the individual may perform ijtihad, but more oriented to the benefit of the people. In social change, religion is only a supplementary function as well as a means for the process of change itself, not religion that makes changes to it. The worlds developing world of its own discretion. Religion only affects the world as far as ready influenced, not more than that. Once religion transformed himself into a decisive, no longer only affect but decisive, then he has become materialistic.